(3QSGdI TYQ GdfaSs - (3CHh EHQGgje ESeGYjd Hf eMeO Hf MGeO GdJejej,J (B420 (3g` s ((3MeRg Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3bGd GdTjN CHhEHQGgje ESeGYjd Hf eMeO GdJejej hEdi ZGjI GdZGjGJ bUOj hoHZjJj hEdi GdMGce GdYGdj Ydi cd MGce s
(3BNQgG (B:s
(3hCTGY HfSNI ddoeSJLjHjf fLR hGdSdGe HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: 27s
(3QSGdI ef QSGFd GdOQhRs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B378s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI aj HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds